2-Hydroxycinnamaldehyde Inhibits SW620 Colon Cancer Cell Growth Through AP-1 Inactivation - Chung Woo Lee (Journal of Pharmacological Sciences, 2007)
Cinnamaldehyde derivatives isolated from Cinnamomum cassia have been widely used for treating dyspepsia, gastritis, and inflammatory disease as well as cancer. To investigate the anti-tumor activities of several cinnamaldehyde derivatives, we compared the inhibitory effect of cinnamaldehyde derivatives on cell growth and AP-1 transcriptional activity in SW620 human colon cancer cells since AP-1 is a transcriptional factor implicated to control cancer cell growth. Among the derivatives, 2’-hydroxycinnamaldehyde (HCA) most significantly inhibited cancer cell growth and AP-1 transcriptional activity in a dose-dependent manner with an IC50 value of 12.5 and 9 µg/ml, respectively. In further studies on the mechanism, we found that consistent with the inhibitory effect on cell growth, HCA dose-dependently (0 – 20 µg/ml) inhibited DNA binding activity of AP-1 accompanied with down regulation of c-Jun and c-Fos expressions. HCA also induced apoptotic cell death as well as expression of the apoptosis-regulating gene caspase-3, but inhibited the anti-apoptosis regulating gene bcl-2 in a dose-dependent manner. These results suggested that HCA has the most potent inhibitory effect against human colon cancer cell growth, and AP-1 may be an important target of HCA. Keywords:: 2’-hydroxycinnamaldehyde (HCA), AP-1, colon cancer, cell growth inhibition